Globalization and health: results and options - Cornia Giovanni Andrea (The World Health Organization, 2001)
The last two decades have witnessed the emergence and consolidation of an economic paradigm which emphasizes domestic deregulation and the removal of barriers to international trade and finance. If properly managed, such an approach can lead to perceptible gains in health status. Where markets are non-exclusionary, regulatory institutions strong and safety nets in place, globalization enhances the performance of countries with a good human and physical infrastructure but narrow domestic markets. Health gains in China, Costa Rica, the East Asian "tiger economies" and Viet Nam can be attributed in part to their growing access to global markets, savings and technology. However, for most of the remaining countries, many of them in Africa, Latin America and Eastern Europe, globalization has not lived up to its promises due to a combination of poor domestic conditions, an unequal distribution of foreign investments and the imposition of new conditions further limiting the access of their exports to the OECD markets. In these developing countries, the last twenty years have brought about a slow, unstable and unequal pattern of growth and stagnation in health indicators. Autarky is not the answer to this situation, but neither is premature, unconditional and unselective globalization. Further unilateral liberalization is unlikely to help them to improve their economic performance and health conditions. For them, a gradual and selective integration into the world economy linked to the removal of asymmetries in global markets and to the creation of democratic institutions of global governance is preferable to instant globalization.